Sebaran jenis Fitoplankton pada Ekosistem Mangrove, Lamun dan Terumbu Karang di Perairan Sekotong Barat, Lombok Barat - Aina Ul Mardiati; Dining Aidil Candri; Sri Puji Astuti; Hilman Ahyadi; Sukiman (Postgraduate, University of Mataram, 2025)
The West Sekotong coastal area, which includes mangrove, seagrass, and coral reef ecosystems, is rich in marine biota, particularly phytoplankton communities. These ecosystems have been designated as conservation areas; however, increasing exploitation and disturbances in the region have impacted the presence and distribution of phytoplankton. This study aimed to assess the distribution, abundance, and species diversity of phytoplankton across these three ecosystems. Using purposive sampling, phytoplankton communities were identified microscopically, revealing a total of 742 phytoplankton cells, with 264 cells in the mangrove, 258 cells in seagrass, and 220 cells in the coral reef ecosystems. The class Bacillariophyceae dominated across all ecosystems. Specific species dominance varied, with Skeletonema costatum prevailing in mangroves, Nitzschia sigmoidhea in seagrass, and Coscinodiscus radiatus in coral reefs. The highest similarity index (35.89%) was observed between mangrove and seagrass ecosystems, while the lowest (30.87%) occurred between mangrove and coral reefs. The species richness index (R) was high in all ecosystems, ranging from 6.45 to 10.26, and dominance indices were low, indicating a balanced community structure. Environmental parameters measured across the ecosystems showed no significant differences and met the quality standards for marine biota as per KEPMENLH No 51 2004.